Notice of the discovery of a beautiful enamelled gold ring, believed to have belonged to King James V., found in the ruins of Tantallan Castle (Proceedings of the Society of Antiquaries of Scotland, 1854)
Captain Henry James exhibited a gold ring that he bought from a surveyor who found it in Tantallon Castle. He describes the decoration on the ring, including the initials 'J. R.' and he notes that if these initials stood for 'James Rex' the ring could have belonged to one of Scotland's Stuart kings. Captain James argues that it may have belonged to James IV and then James V based on documentary evidence that the Queen of France gave James IV a ring not long before he died. At the meeting it was suggested that the initials might read 'I. K.' and that some of its design features indicated it might be older than the sixteenth century.